UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI METODE INKUIRI YANG MENGGUNAKAN KOMIK BIOLOGI SISWA KELAS VII A MTs NEGERI METRO TAHUN PELAJARAN 2011/2012 - Wahyuningsih, Hesty (Bioedukasi Jurnal Pendidikan Biologi, 2013)
The purposes of this research were (1) to improve studentsâ learning activity by using inquiry method with biology comics for the students of VII A MTs Negeri Metro (2) to improve studentsâ achievement in learning biology by using inquiry method with biology comics for the students of VII A MTs Negeri Metro. The results of this research were (1) learning through inquiry method which uses biology comics can improve studentsâ activity during the learning process. From the data of observation, the students achievements increase from cycle I to cycle II (from 46.6% to 55.28%), it means that the increasing is about 8.68% (2) learning through inquiry method which uses biology comics can improve studentsâ activity during the learning process, the students achievements increase from cycle II to cycle III (from 60% to 76.7%), it means that the increasing is about 16, 7%.Â Kata kunci: metode inkuiri, media komik biologi, aktivitas belajar, hasil belajar biologi